Separation of water-oil emulsion by using membrane - Hon, Vai Yee; How, Lian Lee; Yunan, Mat Hussin; Ismail, Ahmad Fauzi (Faculty of Chemical and Natural Resources Engineering, UTM, 2001)
Separation operation has been done to get the crude oil, which is free of emulsion. Membranes are primarily used for separation and membrane processes are generally separation processes. Large-scale commercial uses of membrane separation have displaced conventional separation processes. Studies and testing has been performed on polysulphone flat sheet membrane crossflow ultrafiltration system. The effects of reject flow rate and feed pressure on the water-in-oil emulsion separation was observed. At constant flow rate, filtration rate and flux increase with pressure due to the effect of pressure difference across the membrane affects the present of a higher strength to force the permeate to flow through the membrane. While at constant pressure, the higher the flowrate resulted in the higher filtration rate and flux due to thinner cake layer build up on the membrane which decrease the resistance to the permeate stream to flow through the membrane. The purity of the permeate oil had been tested and also has shown to be free of water.